A systematic review and meta-analysis of the effect of dispatcher-assisted CPR on outcomes from sudden cardiac arrest in adults and children. (May 2019) - Nikolaou, Nikolaos; Dainty, Katie N.; Couper, Keith; Morley, Peter; Tijssen, Janice; Vaillancourt, Christian; ,
Abstract: Background: Dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) has been reported in individual studies to significantly increase the rate of bystander CPR and survival from cardiac arrest. Methods: We undertook a systematic review and meta-analysis to evaluate the impact of DA-CPR programs on key clinical outcomes following out-of-hospital cardiac arrest. We searched the PubMED, EMBASE, CINAHL, ERIC and Cochrane Central Register of Controlled Trials databases from inception until July 2018. Eligible studies compared systems with and without dispatcher-assisted CPR programs. The results of included studies were classified into 3 categories for the purposes of more accurate analysis: comparison of outcomes in systems with DA-CPR programs, case-based comparison of DA-CPR to bystander CPR, and case-based comparisons of DA-CPR to no CPR before EMS arrival. The GRADE system was used to assess certainty of evidence at an outcome level. We used random-effects models to produce summary effect sizes across all outcomes. Results: Of 5531 citations screened, 33 studies were eligible for inclusion. All included studies were observational. Evidence certainty across all outcomes was assessed as low or very low. In system-level and patient-level comparisons, the provision of DA-CPR compared with no DA-CPR was consistently associated with improved outcome across all analyses. Comparison of DA-CPR to bystander CPR produced conflicting results. Findings were consistent across sensitivity analyses and the pediatric sub-group. Conclusion: These results support the recommendation that dispatchers provide CPR instructions to callers for adults and children with suspected OHCA. Review registration: PROSPERO- CRD42018091427.